Pengaruh Kompensasi, Lingkungan Kerja, Dan Motivasi Kerja Terhadap Kinerja Karyawan Divisi Sentra UMKM PT Bank Central Asia Di Kota Semarang - Harsanto, Andreas Dela Hoya; Ferijani, Agatha (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to investigate the influence of compensation, work environment, and motivation on employee performance in the SME Center Division of PT Bank Central Asia in Semarang. Data were collected through questionnaires from 35 respondents working in the division. The results of data analysis using linear regression and statistical tests show that the three independent variables, namely compensation, work environment, and motivation, have a significant positive influence on employee performance. Fair and adequate compensation, a good work environment, and high work motivation encourage employees to perform better. These findings provide insights for companies to develop more effective human resource management strategies to enhance employee performance. Keywords : Compensation, Work Environment, Motivation, Employee Performance, PT Bank Central Asia